Identification and characterization of novel anticancer molecules from various animals - Shareni, Jeyamogan (2020)
The mortality and morbidity of cancer cases has remained significant despite advances in therapeutic interventions and supportive care suggesting the need for new and more effective anticancer agents. Animals such as crocodiles, feed on germ infested meat, are often exposed to carcinogenic heavy metals and withstand extreme levels of radiation, are among the very few species that survived the catastrophic Cretaceous-Tertiary extinction event, and yet they are able to live up to 100 years. Hence, it is postulated that animals living in polluted environments such as crocodiles have developed mechanisms and/or possess molecules against cancer development. In this study, 9 species of vertebrates and 12 species of invertebrates were procured and dissected. Using organ lysates and sera/haemolymph of these animals, growth inhibition assays and cytotoxicity assays were performed on human prostate cancer cells, cervical adenocarcinoma cells, breast adenocarcinoma cells and normal human skin cells. The results revealed that sera of reptiles exhibited irreversible growth inhibition and cytotoxic effects against cancer cells. Reptile sera were then subjected to Liquid chromatography–mass spectrometry and 9 molecules were identified from V. salvator, 20 molecules from R. malayanus, 9 molecules from C. kamaroma amboinensis, 19 molecules from Crocodylus porosus. The presence of more than 100 potential anticancer peptides were also predicted. The sera of C. porosus also demonstrated differentially expressed genes which favours apoptosis and growth inhibition in cancer cells as compared to normal cells. Selected purified molecules were tested against cancer cell lines and exhibited inhibitory properties. These findings are highly significant and provide the basis for development of therapeutic interventions. The molecular identity of the unidentified molecules using analytical approaches, in vivo effects of the identified molecules together with their mode of action is the subject of future studies which will pave the way for the development of new anticancer agents.